2017
DOI: 10.2527/jas2016.0892
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that gene expression of ovarian follicular tight junction proteins is regulated in vivo and in vitro in cattle

Abstract: Tight junctions (TJ) are common paracellular sealing structures that control the transport of water, ions, and macromolecules across cell layers. Because the role of TJ in bovine follicular development is unknown, we investigated the developmental and hormonal regulation of the transmembrane TJ protein, occludin (OCLN), and the cytoplasmic TJ proteins, TJ protein 1 (TJP1) and cingulin (CGN) in bovine granulosa cells (GC) and theca cells (TC). For this purpose, bovine GC and TC were isolated from large (>8 mm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…1D), and in vivo inhibition of VEGFA using soluble recombinant VEGF receptor proteins caused a decrease in theca CLDN5 protein and an increase in granulosa OCLN protein in and CGN mRNA in bovine theca cells (Zhang et al 2017). Previously, we reported that TC had 375 greater OCLN and TJP1 mRNA than GC whereas GC had greater CGN mRNA than TC of bovine follicles (Figure 2A; Zhang et al 2017). Therefore we conducted an additional study to determine if abundance of CGN mRNA in GC differed among estrogen-active and estrogen-378 inactive small, medium and/or large follicles in cattle, and found that there were no significant differences in GC CGN mRNA expression among estrogen-inactive follicles of different sizes ( Figure 2B).…”
Section: Tj Proteins and Ovarian Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…1D), and in vivo inhibition of VEGFA using soluble recombinant VEGF receptor proteins caused a decrease in theca CLDN5 protein and an increase in granulosa OCLN protein in and CGN mRNA in bovine theca cells (Zhang et al 2017). Previously, we reported that TC had 375 greater OCLN and TJP1 mRNA than GC whereas GC had greater CGN mRNA than TC of bovine follicles (Figure 2A; Zhang et al 2017). Therefore we conducted an additional study to determine if abundance of CGN mRNA in GC differed among estrogen-active and estrogen-378 inactive small, medium and/or large follicles in cattle, and found that there were no significant differences in GC CGN mRNA expression among estrogen-inactive follicles of different sizes ( Figure 2B).…”
Section: Tj Proteins and Ovarian Functionmentioning
confidence: 99%
“…CLDN5 protein localizes around granulosa cells in marmoset preantral follicles (Fig. 1D), and in vivo inhibition of VEGFA using soluble recombinant VEGF receptor proteins caused a decrease in theca CLDN5 protein and an increase in granulosa OCLN protein in and CGN mRNA in bovine theca cells (Zhang et al 2017). Previously, we reported that TC had 375 greater OCLN and TJP1 mRNA than GC whereas GC had greater CGN mRNA than TC of bovine follicles (Figure 2A; Zhang et al 2017).…”
Section: Tj Proteins and Ovarian Functionmentioning
confidence: 99%
See 3 more Smart Citations